Persistent Effects of Temporary Incentives: Evidence from a Nationwide Health Insurance Experiment - Aurélien Baillon; Joseph Capuno; Owen O'Donnell; Carlos Tan; Kim van Wilgenburg (Tinbergen Institute, 2019)
Temporary incentives are offered in anticipation of persistent effects, but these are seldom estimated. We use a nationwide randomized experiment in the Philippines to estimate effects three years after the withdrawal of two incentives for health insurance. A premium subsidy had a persistent effect on enrollment that is more than four fifths of the immediate effect. Application assistance had a much larger immediate impact, but less than a fifth of this effect persisted. The subsidy persuaded those with higher initial willingness to pay to enroll and keep enrolling, while application assistance achieved a larger immediate effect by drawing in those who valued insurance less and were less likely to re-enroll.
Keywords: I13; C93; 330; incentives; persistence; health insurance; subsidy; randomized experiment